Development of Augmented Reality Learning Media for Computer Network Topics in Junior High School (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study aimed to develop and analyze the effectiveness of Augmented Reality (AR)-based learning media for computer network topics at the junior high school level. The background of this research is based on students’ difficulties in understanding abstract computer network concepts when taught using conventional methods. Method: The research employed a Research and Development approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. AR learning media were developed using paper-based markers that can be scanned via smartphones to display interactive three-dimensional representations of computer network components. Result: The research subjects were ninth-grade students and information and communication technology teachers. Data were collected through observations, questionnaires, and learning outcome assessments. The results indicate that the AR-based learning media were validated by material and media experts and were considered practical for classroom implementation. Furthermore, AR media significantly improved students’ conceptual understanding and learning engagement compared to conventional instructional methods. Novelty: This study introduces innovation through the development of AR learning media that transform abstract concepts of computer networks, which are usually difficult to visualize, into interactive three-dimensional objects that can be directly manipulated by students. Unlike previous research that generally targets higher education or general hardware materials, this study specifically integrates the junior high school informatics curriculum with an ADDIE-based instructional design that emphasizes active engagement and conceptual understanding of students through personal mobile devices.